Unique structure (construction and configuration) and evolution of the array of small serum protein genes of Protobothrops flavoviridis snake * - Chijiwa, Takahito (Biosci Rep, 2019)
The nucleotide sequence of Protobothrops flavoviridis (Pf) 30534 bp genome segment which contains genes encoding small serum proteins (SSPs) was deciphered. The genome segment contained five SSP genes (PfSSPs), PfSSP-4, PfSSP-5, PfSSP-1, PfSSP-2, and PfSSP-3 in this order and had characteristic configuration and constructions of the particular nucleotide sequences inserted. Comparison between the configurations of the inserted chicken repeat-1 (CR1) fragments of P. flavoviridis and Ophiophagus hannah (Oh) showed that the nucleotide segment encompassing from PfSSP-1 to PfSSP-2 was inverted. The inactive form of PfSSP-1, named PfSSP-1δ(Ψ), found in the intergenic region (I-Reg) between PfSSP-5 and PfSSP-1 had also been destroyed by insertions of the plural long interspersed nuclear elements (LINEs) and DNA transposons. The L2 LINE inserted into the third intron or the particular repetitive sequences inserted into the second intron structurally divided five PfSSPs into two subgroups, the Long SSP subgroup of PfSSP-1, PfSSP-2 and PfSSP-5 or the Short SSP subgroup of PfSSP-3 and PfSSP-4. The mathematical analysis also showed that PfSSPs of the Long SSP subgroup evolved alternately in an accelerated and neutral manner, whereas those of the Short SSP subgroup evolved in an accelerated manner. Moreover, the ortholog analysis of SSPs of various snakes showed that the evolutionary emerging order of SSPs was as follows: SSP-5, SSP-4, SSP-2, SSP-1, and SSP-3. The unique interpretation about accelerated evolution and the novel idea that the transposable elements such as LINEs and DNA transposons are involved in maintaining the host genome besides its own transposition natures were proposed.